V‐myb avian myeloblastosis viral oncogene homolog expression is a potential molecular diagnostic marker for B‐cell acute lymphoblastic leukemia. Issue 1 (10th August 2020) - Caballero‐Palacios, Marcela Concepción; Villegas‐Ruiz, Vanessa; Ramírez‐Chiquito, Josselen Carina; Medina‐Vera, Isabel; Zapata‐Tarres, Martha; Mojica‐Espinosa, Raúl; Cárdenas‐Cardos, Rocio; Paredes‐Aguilera, Rogelio; Rivera‐Luna, Roberto; Juárez‐Méndez, Sergio
Abstract: Background: B‐cell acute lymphoblastic leukemia (B‐ALL) is the most commonly diagnosed childhood malignancy worldwide and is especially common in Mexico. Additionally, the number of cases has increased in recent years. Thus, it is very important to develop molecular strategies to diagnose leukemia. The aim of this study was to investigate MYB expression and to determine its impact on the diagnosis of B‐ALL. Methods: We analyzed the B‐ALL gene expression profile by microarray data mining. Bioinformatics analysis was performed to identify the genes that are overexpressed in leukemia. We determined that MYB was highly expressed in leukemia. Then, we validated MYB expression in 70 patients with B‐ALL and in 16 healthy controls (HCs) using qRT‐PCR. The results were statistically analyzed using the Kolmogorov‐Smirnov Z test, Mann‐Whitney U test, receiver operating characteristic curves, and the Youden index. Results: The microarrays showed that MYB was overexpressed in B‐ALL patients with a fold change of 57.8728 and a P value of 2.56 −195 . MYB expression showed great variability among the patients analyzed. However, compared to the HCs, the B‐ALL patients had a P value < .0001, an area under the curve of 0.813, and a Youden index of 1.46, indicating the statistical significance. Conclusion: MYB expression in B‐ALL cells could be a potential molecular marker for childhood leukemia.